Self-report to self-control? : A note - Baumann, Florian; Friehe, Tim (My University, 2012)
This note establishes that escalating penalty regimes with the option to self-report crimes may allow present-biased offenders to obligate themselves to refrain from committing future crimes. Self-reporting of a committed crime increases the expected costs of future criminal opportunities, possibly allowing offenders to deter their future selves from seeking immediate gratification.
Keywords: 330